What Do We Know About the Chevrel Technique in Ventral Incisional Hernia Repair? - Köckerling, Ferdinand (Frontiers in Surgery, 2019)
Introduction: In publications on ventral incisional hernia repair, the Chevrel technique and the onlay operation are often equated. This present review now aims to present the difference between these surgical techniques and analyze the findings available on the Chevrel technique. Materials and Methods: A systematic search of the available literature was performed in January 2019 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library, as well as a search of relevant journals, books, and reference lists. Thirty-four publications were identified as relevant for this review. For assessment of the Chevrel-technique with other surgical procedures there are no randomized controlled trials, prospective or retrospective comparative studies available but only case series. In the majority of case series the follow-up procedure is not reported. Results: In the onlay technique the defect is closed with direct suture or it is omitted altogether. Whereas, in the Chevrel technique this is done with sliding myofascial flaps harvested from the rectus sheaths. In the few case series available this appears to result in a lower recurrence rate for the Chevrel technique compared with the onlay technique. However, the rates of postoperative complications, surgical site occurrences (SSOs), surgical site infections (SSIs), seroma, and skin necrosis are as high as in the onlay technique. The reason for this is that both techniques require subcutaneous undermining with severance of perforator vessels. Conclusion: If mesh placement in onlay position has been chosen for specific reasons, preference can be given to the Chevrel technique over the standard onlay technique, although the study quality is limited.